The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.2337/diacare.21.4.539
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Long-Term Risk of Mortality From Coronary and Other Causes in Middle-Aged Swedish Men: A general population study

Abstract: In men with diabetes, hypercholesterolemia, smoking, and hypertension predict coronary mortality risk, as well as mortality risk from all causes. Men with both diabetes and hypercholesterolemia have severely compromised survival and should be targeted for intervention aimed at lowering their lipid levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 30 publications
(69 reference statements)
6
50
2
Order By: Relevance
“…Findings in those that have are inconsistent. Several analyses have reported similar associations between total cholesterol or LDL-cholesterol and cardiovascular outcomes in patients with and without diabetes [2,4,11,12]. However, in the largest analysis conducted to date [3], the relationship between total cholesterol and risk of CVD in people with diabetes was reported to be weaker than that among individuals without diabetes (13 vs 28% excess risk of CVD associated with a 1 mmol/l increase in the level of total cholesterol), although it is not clear whether this difference was statistically significant.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Findings in those that have are inconsistent. Several analyses have reported similar associations between total cholesterol or LDL-cholesterol and cardiovascular outcomes in patients with and without diabetes [2,4,11,12]. However, in the largest analysis conducted to date [3], the relationship between total cholesterol and risk of CVD in people with diabetes was reported to be weaker than that among individuals without diabetes (13 vs 28% excess risk of CVD associated with a 1 mmol/l increase in the level of total cholesterol), although it is not clear whether this difference was statistically significant.…”
Section: Discussionmentioning
confidence: 91%
“…The major importance of diabetes mellitus as an independent risk factor for cardiovascular disease (CVD) is well established and consistent across populations [1,2]. Diabetes is associated with a two-to fourfold risk of cardiovascular events and cardiovascular death [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…36) to 100%. 37 The covariables accounted for in the analyses included ethnicity, 37,39 sex, [36][37][38][39][40] age, [36][37][38][39][40] body mass index, 36,39,40 smoking, [36][37][38]40 alcohol intake, 40 physical activity, 40 education, 40 history of cardiovascular disease, 36,39 serum cholesterol, 36,37,39,40 or albuminuria. 37 Masked hypertension was associated with increased risk both in non-diabetic subjects and in patients with diabetes, without any significant interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Comments have been made on the inconsistences in the findings of these studies even regarding the role of the classical CVD risk factors, blood pressure, serum cholesterol and cigarette smoking [2]. Of these only one small study was negative [25]; the largest one involving patients screened for the Multiple Risk Factor Intervention Trial (MRFIT) [14], the UK Prospective Diabetes Study (UKPDS) [52] and our study have clearly shown that all these three risk factors are predictive of CVD mortality in patients with Type II diabetes.…”
Section: Discussionmentioning
confidence: 99%